Appropriateness of Tympanostomy Tubes in the Boston Metropolitan Area: Are the AAO-HNSF Guidelines Being Met?. (December 2017) - Hughes, Amy L.; Roberson, David; Bannos, Cassandra; Trudell, Emily K.; Vernacchio, Louis
Introduction: Otitis media (OM) is the most common reason children receive general anesthesia, with bilateral tympanostomy tube (TT) insertion the second most common surgery in children. Prior research suggests overuse of TT. As part of a project designed to improve appropriateness of OM referrals, we evaluated appropriateness of TT insertion in a patient cohort. Methods: Patients younger than 9 years with initial otolaryngology (ORL) visits in academic and private office settings for OM from January 1, 2012, to August 31, 2013, were identified through claims database. A detailed retrospective chart review of patients undergoing TT insertion was performed to determine appropriateness of TT insertion per the 2013 American Academy of Otolaryngology—Head and Neck Surgery Foundation (AAO-HNSF) guidelines. Results: A total of 120 patients undergoing TT insertion were randomly chosen for detailed chart review; 32 patients were excluded. Sixty-six (75%) of 88 patients available for analysis met AAO-HNSF guidelines for TT. Recurrent acute OM with middle ear effusion was the most common indication (56%). Other indications included chronic OME and TT in at-risk patients with speech, learning, or behavioral delays. Of the 22 patients undergoing TT insertion not meeting AAO-HNSF guidelines, 11(50%) had abnormal exams, but were 1 to 2 infections short of meeting guidelines; 7 (33%) had normal exams but met criteria for number of infections. Discussion: Contrary to prior publications, 75% of patients undergoing TT insertion had an appropriate indication per AAO-HNSF guidelines. In only 5% was TT insertion a substantial departure from guidelines. Implications for Practice: The study outcomes suggest appropriate clinical decision making, improved guideline adherence, and better guideline applicability from the previously published 1994 and 2004 guidelines.